2009
DOI: 10.1111/j.1939-1676.2008.0235.x
|View full text |Cite
|
Sign up to set email alerts
|

Ki‐67 and Vascular Endothelial Growth Factor Expression in Intracranial Meningiomas in Dogs

Abstract: Background: Tumor proliferation in human intracranial meningiomas can be defined by the reactivity of the monoclonal antibody MIB-1 to the Ki-67 antigen. Vascular endothelial growth factor (VEGF), a pro-angiogenic factor, is a predictive marker for survival of dogs with intracranial meningiomas.Hypothesis: Ki-67 is expressed in canine intracranial meningiomas and is associated with VEGF expression. Ki-67 expression is a prognostic marker for patient outcome.Animals: Seventy client-owned dogs with WHO grade I i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
24
0
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 52 publications
1
24
0
2
Order By: Relevance
“…O índice médio de proliferação celular foi de 3,4% para a expressão de Ki-67 e de 3,2 figuras de mitose em 10 campos de grande aumento. A variação nos índices proliferativos (Ki-67) e, em alguns casos, ausência de marcação nos meningiomas já foi previamente descrita (Matiasek et al 2009). Variações na intensidade de marcação da proteína Ki-67 podem também ocorrer dentro de um mesmo subtipo histológico (Isolan et al 2005).…”
Section: Resultsunclassified
See 1 more Smart Citation
“…O índice médio de proliferação celular foi de 3,4% para a expressão de Ki-67 e de 3,2 figuras de mitose em 10 campos de grande aumento. A variação nos índices proliferativos (Ki-67) e, em alguns casos, ausência de marcação nos meningiomas já foi previamente descrita (Matiasek et al 2009). Variações na intensidade de marcação da proteína Ki-67 podem também ocorrer dentro de um mesmo subtipo histológico (Isolan et al 2005).…”
Section: Resultsunclassified
“…De modo geral, os índices proliferativos nos meningiomas caninos, tanto em relação ao número de figuras de mitose (Schulman et al 1992) como na expressão de Ki-67 são relativamente baixos, com índice médio de proliferação de 1,8% (Matiasek et al 2009). Outro aspecto interessante é que a baixa proliferação celular não está associada a um melhor prognóstico para o animal (Matiasek et al 2009). …”
Section: Resultsunclassified
“…Veterinary trials with toceranib and masitinib have shown benefit in several cancers but have not been reported for brain tumors. Documented overexpression of VEGF, VEGF receptors, and PDGFR alpha in some canine brain tumors108, 109, 110, 111, 112, 113, 114, 115, 116 may justify trials with these or similar small molecules in defined patients.…”
Section: Novel Therapiesmentioning
confidence: 99%
“…It also stimulates abnormal angiogenesis in solid tumour growth and metastasis (Ribatti et al, 1999;Takanami et al, 2000;Elpek et al, 2001;Ranieri et al, 2002Ranieri et al, , 2003Iamaroon et al, 2003;Kondo et al, 2006;Tuna et al, 2006). VEGF expression has been evaluated in canine mammary carcinoma Qiu et al, 2008), seminoma (Restucci et al, 2003), intracranial meningioma (Matiasek et al, 2009) and lymphoma (Gentilini et al, 2005;Wolfesberger et al, 2007Wolfesberger et al, , 2008. Crosstalk between VEGF and MMPs has recently been described: VEGF signalling via VEGFR-2 induces the expression of MMP-2, MMP-9 and MT1-MMP, which degrade the matrix to allow for endothelial sprouting (Funahashi et al, 2011).…”
Section: Introductionmentioning
confidence: 98%